Global Trends and Emerging Themes in Sleep Disorders Research in Chronic Kidney Disease: A Bibliometric Analysis - Fauziah, Hesti Fathan Nurfais; Rochmawati, Erna (Universitas Respati Yogyakarta, 2025)
Sleep disorders are common in chronic kidney disease (CKD), significantly impairing quality of life and accelerating disease progression. Despite growing research, no comprehensive bibliometric analysis has been conducted on this topic. This research contributed to analyzing global research trends and identifying emerging themes in sleep disorders research in CKD patients from 2014 to 2024. A bibliometric analysis of publications in the Scopus database was performed, with visualization, co-occurrence, and trend analyses conducted using VOS viewer software (version 1.6.20). From 516 publications indicated increasing research activity despite periodic fluctuations. The United States was the leading contributor. Key emerging themes included the impact of dialysis on sleep disorders, physical and mental health, and quality of life; pathophysiological mechanisms of sleep regulation in CKD; comorbidities and risk factors exacerbating sleep disorders; and the types of sleep disorders and their effects on mortality and morbidity in CKD patients. Future directions emphasize technology-based monitoring, psychosocial interventions, personalized medicine approaches, and innovations in dialysis therapies. This first comprehensive bibliometric analysis provides insights into global research trends and key emerging themes on sleep disorders in CKD, guiding clinicians in holistic care and researchers in addressing literature gaps to improve patient outcomes.